Tetraphenylethylene-based polymer, preparation method thereof and application of tetraphenylethylene-based polymer in display device
By introducing tetraphenyl vinyl groups and long alkyl chains into the polymer, a tetraphenyl vinyl polymer with high contrast and discoloration stability was prepared, and the contrast of polymer electrochromic materials was solved. The problem of poor results enables efficient application in display devices.
Patent Information
- Application Number
- CN202411804942.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-18
AI Technical Summary
The current poor contrast effect of polymer electrochromic materials limits its application performance in high-resolution display, fine information transmission, and complex environmental monitoring.
By introducing tetraphenyl vinyl groups into the polymer, a tetrastyrene polymer with electroluminescence function is prepared, and by introducing propylene dioxythiophene units with long alkyl chains, the discoloration stability and dissolution of the material are improved by introducing the propylene dioxythiophene units of long alkyl chains. sex.
Improve the contrast and color change stability of the material, ensure good performance can be maintained after multiple electrochemical cycles, achieve long-lived, high-reliability tetrastyrene-based polymers, and reduce film preparation costs, improve The coating uniformity and quality of the film are achieved.
Smart Images

Figure CN119463133A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organic polymers, and in particular to a tetraphenylethylene-based polymer, a preparation method thereof, and an application thereof in a display device. Background Art
[0002] Electrochromism (EC) is a phenomenon in which a material undergoes a reversible change in color or transparency due to a redox reaction under the stimulation of an applied voltage. Electrochromic materials have been widely studied and applied due to their ideal physical and chemical properties, including high-contrast optical response, fast switching time, long-term stability and high quantum yield. Therefore, they have broad application potential in optical display, information encryption, military camouflage, sensors, and smart windows.
[0003] Electrochromic materials are mainly divided into two categories: small molecules and polymers. Among them, polymer electrochromic materials allow the absorption and emission characteristics of light to be controlled by precise chemical synthesis due to the adjustable band gap, thereby achieving precise control of the luminescent color. This not only gives polymer electrochromic materials excellent performance in optical and electrical properties, but also makes them have excellent mechanical strength and physical stability, further improving the durability and service life of the material.
[0004] At present, polymer-based electrochromic materials are gradually becoming a hot topic in the field of scientific research, attracting widespread attention and research. Experimental data and research results show that under different electrochemical states, polymer-based electrochromic materials will show unique optical properties: the appearance color and light transmittance of polymer materials will change significantly, so that the material can continuously change from a transparent state to a colored state under the action of an electric field, showing electrochromic properties. In addition, polymer electrochromic materials have excellent processing properties and are easy to mass produce. They are particularly suitable for manufacturing large-area flexible films, opening a new chapter in multifunctional smart materials.
[0005] However, although polymer electrochromic materials have shown great potential in the field of smart materials, they still face many challenges in the preparation process of their actual application in electrochromic devices. Ideally, polymers should show significant color changes between oxidized and reduced states to ensure high-contrast display effects. However, most polymer materials currently do not perform well in this regard, which directly restricts the application efficiency of polymer electrochromic materials in fields such as high-resolution display, fine information transmission, and complex environmental monitoring. Summary of the invention
[0006] The object of the present invention is to provide a tetraphenylethylene-based polymer and a preparation method thereof and application in a display device, so as to solve the problem of poor contrast effect of current polymer electrochromic materials.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides a tetraphenylethylene polymer having a structure shown in Formula I:
[0009]
[0010] Wherein, n=20-1000, and n is an integer.
[0011] The present invention provides a method for preparing the above tetraphenylethylene polymer, comprising the following steps:
[0012] Mixing a monomer having a structure represented by formula II and a compound having a structure represented by formula Ш with an alkali reagent, an additive, a catalyst, and an organic solvent to carry out an arylation polycondensation reaction to obtain a tetraphenylethylene polymer;
[0013]
[0014] Preferably, the mass ratio of the monomer having the structure shown in formula II to the compound having the structure shown in formula Ш is 1-2:1; the alkaline reagent includes potassium carbonate or sodium carbonate; the additive includes pivalic acid or pivalic acid; the catalyst includes palladium acetate or tetrakistriphenylphosphine palladium; the mass ratio of the alkaline reagent, the additive, the catalyst and the compound having the structure shown in formula III is 1.17-1.5:1:1.43-2:1.5-2; the organic solvent includes DMAc or DMF.
[0015] Preferably, the temperature of the arylation polycondensation reaction is 125-135° C. and the time is 12-20 hours.
[0016] The present invention provides application of the tetraphenylethylene based polymer or the tetraphenylethylene based polymer prepared by the above preparation method in a display device.
[0017] Preferably, the tetraphenylethylene polymer is used in a display device in the form of an electrochromic film.
[0018] Preferably, the electrochromic film comprises a substrate and an electrochromic layer supported on the substrate; the material of the electrochromic layer is the above-mentioned tetraphenylethylene polymer or the tetraphenylethylene polymer prepared by the above-mentioned preparation method.
[0019] Preferably, the substrate comprises indium tin oxide conductive glass, fluorine tin oxide conductive glass or polyethylene terephthalate conductive substrate.
[0020] Preferably, the electrochromic layer is formed on the surface of the substrate by solution processing film forming.
[0021] Preferably, the solvent used in the solution processing film-forming method includes dichloromethane, chloroform, tetrahydrofuran, toluene or dimethylformamide.
[0022] Beneficial effects of the present invention:
[0023] The present invention introduces tetraphenylethylene groups into the polymer, so that the material has an electroluminescent function and improves the contrast of the material, so that such material can be applied to the field of encrypted display; by introducing propylene dioxythiophene units with long alkyl chains, not only the color change stability of the bifunctional polymer is improved, ensuring that the material can still maintain good performance after undergoing multiple electrochemical cycles, thereby obtaining a tetraphenylethylene-based polymer with long life and high reliability, but also the solubility of the bifunctional polymer material is increased, the cost of film preparation is greatly reduced, and the coating uniformity and quality of the film are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the infrared spectrum of PPTPATPE prepared in Example 1;
[0025] Figure 2 The cyclic voltammetry curve of the PPTPATPE film prepared in Example 2 at 0-1.2V;
[0026] Figure 3 This is the UV-visible absorption spectrum of the PPTPATPE film prepared in Example 2 at 0-1.2V;
[0027] Figure 4 The transmittance variation curve of the PPTPATPE film prepared in Example 2 at 410nm band under different cycle times;
[0028] Figure 5 The response time kinetic change curve of the PPTPATPE film prepared in Example 2 at 410nm band at different times;
[0029] Figure 6 The transmittance variation curve of the PPTPATPE film prepared in Example 2 at 600nm band under different cycle times;
[0030] Figure 7 The response time kinetic change curve of the PPTPATPE film prepared in Example 2 in the 600nm band at different times. DETAILED DESCRIPTION
[0031] The present invention provides a tetraphenylethylene polymer having a structure shown in Formula I:
[0032]
[0033] Among them, n is preferably 20 to 1000 and n is an integer, and n is more preferably 1000.
[0034] In the present invention, unless otherwise specified, the required raw materials for preparation are all commercially available products well known to those skilled in the art.
[0035] The present invention provides a method for preparing the above tetraphenylethylene polymer, comprising the following steps:
[0036] Mixing a monomer having a structure represented by formula II and a compound having a structure represented by formula Ш with an alkali reagent, an additive, a catalyst, and an organic solvent to carry out an arylation polycondensation reaction to obtain a tetraphenylethylene polymer;
[0037]
[0038] The present invention has no particular limitation on the source of the monomer of the structure shown in Formula II, and it can be prepared by methods well known in the art. The method for preparing the monomer of the structure shown in Formula II in the embodiment of the present invention preferably comprises the following steps:
[0039] 0.41 g 1-(4-bromophenyl)-1,2,2-triphenylethylene (1 mmol), 0.83 g potassium carbonate (2 mol / L), 0.50 g 4-triphenylamine boronic acid (1.73 mmol), and tetrakistriphenylphosphine palladium were added to a 100 mL double-necked round-bottom flask, and 20 mL toluene and 5 mL water were added under nitrogen protection at 90° C. to carry out Suzuki coupling reaction. After 26 hours, the mixture was cooled to room temperature, and the organic layer was collected by extraction with dichloromethane, and then dried over anhydrous sodium sulfate, purified by column chromatography, and the elution effect was optimized by changing the ratio of solvents, DCM:PE=1:7 to 1:5 to 1:3, and finally an intermediate product having a structure shown in Formula IV was obtained;
[0040]
[0041] To a 100 mL Shrek tube, add 0.98 g of the intermediate product having the structure shown in Formula IV (1.34 mmol) and 0.52 g of NBS (2.92 mmol), shield from light, add 20 mL of chloroform under a nitrogen atmosphere, and carry out N-bromosuccinimide bromination reaction at 0°C for 2 hours, then stir at room temperature overnight. After the reaction is completed, purify by column chromatography (solvent ratio DCM:PE=1:1) to obtain a monomer having the structure shown in Formula II.
[0042] The present invention has no particular limitation on the source of the compound of the structure represented by the formula Ш, and any commercially available product may be used. In the examples of the present invention, the compound of the structure represented by the formula Ш is specifically sourced from Merck, model number 660523.
[0043] The present invention preferably adds a monomer having a structure shown in formula II, a compound having a structure shown in formula Ш, an alkali reagent, an additive, and a catalyst into a round-necked flask, adds an organic solvent under nitrogen protection, performs an arylation polycondensation reaction, and performs post-treatment and extraction in sequence after the reaction is completed to obtain a tetraphenylethylene polymer.
[0044] In the present invention, the mass ratio of the monomer having the structure represented by formula II to the compound having the structure represented by formula Ш is preferably 1 to 2:1, more preferably 1.5 to 2:1, and more preferably 1.67:1.
[0045] In the present invention, the alkaline reagent preferably includes potassium carbonate or sodium carbonate, and further preferably includes potassium carbonate; the additive preferably includes pivalic acid or neopentanoic acid, and further preferably includes neopentanoic acid; the catalyst preferably includes palladium acetate or tetrakistriphenylphosphine palladium, and further preferably includes palladium acetate; the mass ratio of the alkaline reagent, the additive, the catalyst and the compound having the structure represented by formula Ш is preferably 1.17-1.5:1:1.43-2:1.5-2, and further preferably 1.17-1.2:1:1.43-1.5:1.5-1.8, and further preferably 1.17:1:1.43:1.51.
[0046] In the present invention, the organic solvent preferably includes DMAc or DMF, and more preferably DMAc.
[0047] In the present invention, the temperature of the arylation polycondensation reaction is preferably 125 to 135° C., more preferably 135° C., and the time is preferably 12 to 20 hours, more preferably 13 hours.
[0048] In the present invention, the post-treatment operation is preferably as follows: after the reaction is completed, the obtained mixture is cooled to room temperature, precipitated with methanol, and then filtered to obtain a filtered solid.
[0049] In the present invention, the extraction operation is preferably: subjecting the filtered solid to Soxhlet extraction; the solvent used for the Soxhlet extraction preferably includes methanol, acetone, petroleum ether and chloroform; more preferably, methanol-acetone-petroleum ether-chloroform is used in sequence for extraction; the extraction conditions are preferably methanol extraction time of 24h and temperature of 110°C; acetone extraction time of 24h and temperature of 115°C; petroleum ether extraction time of 20h and temperature of 110°C; chloroform extraction time of 20h and temperature of 118°C.
[0050] The present invention preferably collects the solution obtained by chloroform extraction, and removes the solvent by rotary evaporation through a rotary evaporator to obtain a tetraphenylethylene polymer; the rotary evaporation temperature is preferably 50° C., the time is preferably 5 min, and the pressure is preferably 0.05 MPa.
[0051] The present invention provides application of the tetraphenylethylene based polymer or the tetraphenylethylene based polymer prepared by the above preparation method in a display device.
[0052] In the present invention, the tetraphenylethylene polymer is preferably used in a display device in the form of an electrochromic film; the electrochromic film preferably includes a substrate and an electrochromic layer supported on the substrate; the material of the electrochromic layer is preferably the above-mentioned tetraphenylethylene polymer or the tetraphenylethylene polymer prepared by the above-mentioned preparation method.
[0053] In the present invention, the substrate preferably includes indium tin oxide conductive glass, fluorine tin oxide conductive glass or polyethylene terephthalate conductive substrate, and more preferably indium tin oxide conductive glass.
[0054] In the present invention, the electrochromic layer is preferably formed on the surface of the substrate by solution processing film forming.
[0055] In the present invention, the solvent used in the solution film processing method preferably includes dichloromethane, chloroform, tetrahydrofuran, toluene or dimethylformamide, and further preferably includes chloroform, tetrahydrofuran, toluene, and more preferably includes chloroform. The present invention has no special limitation on the specific method of the solution film processing method, and the method can be processed according to methods well known in the art. In the embodiment of the present invention, spin coating or spray coating is preferably used for film processing.
[0056] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0057] The compounds with the structure shown in the following examples are from Merck, model number 660523.
[0058] Example 1
[0059] 0.41 g 1-(4-bromophenyl)-1,2,2-triphenylethylene (1 mmol), 0.83 g potassium carbonate (2 mol / L), 0.50 g 4-triphenylamine boronic acid (1.73 mmol), and tetrakistriphenylphosphine palladium were added to a 100 mL double-necked round-bottom flask, and 20 mL toluene and 5 mL water were added under nitrogen protection at 90° C. to carry out Suzuki coupling reaction. After 26 hours, the mixture was cooled to room temperature, and the organic layer was collected by extraction with dichloromethane, then dried over anhydrous sodium sulfate, and purified by column chromatography. The elution effect was optimized by changing the ratio of solvents, DCM:PE=1:7 to 1:5 to 1:3, and finally 0.43 g of a yellow solid, i.e., an intermediate product having a structure shown in formula IV, was obtained with a yield of 83%;
[0060] 0.98 g of the intermediate product having the structure shown in Formula IV (1.34 mmol) and 0.52 g of NBS (2.92 mmol) were added to a 100 mL Shrek tube, and 20 mL of chloroform was added under a nitrogen atmosphere to shield the tube from light. The N-bromosuccinimide bromination reaction was carried out at 0° C. for 2 h, and then stirred at room temperature overnight. After the reaction was completed, the mixture was purified by column chromatography (solvent ratio DCM:PE=1:1) to obtain 0.82 g of a yellow solid, i.e., a monomer having the structure shown in Formula II, with a yield of 90%;
[0061] To a 50 mL double-necked round-bottom flask, 0.88 g of a monomer having a structure shown in formula II (1.2 mmol), 0.53 g of a compound having a structure shown in formula III (1.2 mmol), 0.41 g of potassium carbonate (3 mmol), 0.35 g of pivalic acid (3.43 mmol), and 0.5 g of palladium acetate (0.223 mmol) were added. 15 mL of DMAc, after 13h of arylation polycondensation reaction, the obtained mixture was cooled to room temperature and then precipitated with methanol, and the solid obtained by filtration was extracted with methanol, acetone, petroleum ether and chloroform in sequence, and the extraction conditions were as follows: methanol extraction time was 24h and the temperature was 110°C; acetone extraction time was 24h and the temperature was 115°C; petroleum ether extraction time was 20h and the temperature was 110°C; chloroform extraction time was 20h and the temperature was 118°C; the solution obtained by extraction with chloroform was collected, and the solvent was removed by rotary evaporation to obtain 1.0g of tetraphenylethylene polymer (n value was 10000), which was recorded as PPTPATPE.
[0062] Example 2
[0063] 15 mg of the tetraphenylethylene polymer (PPTPATPE) prepared in Example 1 was dissolved in 1 mL of chloroform solvent, ultrasonically dissolved, filtered, and then spin-coated on indium tin oxide conductive glass (0.94 cm) at a speed of 1000 r / min to form a film. The electrochromic film after spraying was placed in a 50°C oven to dry, thereby obtaining a tetraphenylethylene polymer PPTPATPE film.
[0064] Characterization and performance testing
[0065] 1. Infrared characterization
[0066] The infrared absorption spectrum of the tetraphenylethylene polymer obtained in Example 1 was obtained by infrared spectrometer. Figure 1 .
[0067] Depend on Figure 1It can be seen that the CS bond appears in the range of 760cm-1, indicating that there is a bond between the sulfur atom and the carbon atom in the molecule; the CO bond appears in the range of 1050cm-1, indicating that it is combined with the carbon-oxygen single bond in the ester group; the CN bond appears at 1260cm-1, indicating that it is combined with the carbon-nitrogen single bond in the amine group; the C=C double bond and CC single bond appear at 1500cm-1, and the absorption peak of the C=C double bond usually appears at 1600-1680cm-1, while the absorption peak of the CC single bond may be broader, covering the range of 1000-1500cm-1; the unsaturated CH bond appears at 2900cm-1, indicating that it is combined with the carbon-hydrogen bond in the olefin, proving that PPTPATPE is successfully synthesized.
[0068] 2. Performance Testing
[0069] Add 1.064 g of lithium perchlorate (0.1 mol / L) into a 100 mL volumetric flask and dilute to volume with chromatography grade acetonitrile to obtain a blank supporting electrolyte solution;
[0070] The tetraphenylethylene polymer PPTPATPE film obtained in Example 2 was used as a working electrode, a platinum sheet was used as a counter electrode, and Ag / AgCl was used as a reference electrode to test the performance of the PPTPATPE film.
[0071] (1) Cyclic voltammetry performance test.
[0072] The cyclic voltammetry performance of PPTPATPE film was tested at 0-1.2V. The test results are as follows: Figure 2 shown.
[0073] Depend on Figure 2 It can be seen that PPTPATPE has an obvious redox peak, which indicates that PPTPATPE has good redox activity and the redox behavior is reversible.
[0074] (2) UV-visible absorption spectrum test.
[0075] The UV-visible absorption spectrum of PPTPATPE film under different voltages is tested. The test results are as follows: Figure 3 shown.
[0076] Depend on Figure 3 It can be seen that the color of PPTPATPE film is yellow in the neutral state and gray in the oxidized state, with obvious color changes.
[0077] (3) Optical contrast and cyclic stability.
[0078] Optical contrast refers to the maximum value of the change in transmittance of an electrochromic device at a specific wavelength within the operating voltage range before and after switching potential. Cycling stability refers to the number of times the device can switch between coloration and fading before any significant degree of degradation occurs.
[0079] The optical properties of PPTPATPE film at 410nm and 600nm were tested by using UVProbe software using a CHI660E electrochemical workstation and UV-1800 ultraviolet-visible spectrophotometer. The blank supporting electrolyte solution was used as the baseline for the scan. The test results are shown in Figures 4 to 7 .
[0080] Figure 4 The transmittance variation curve of PPTPATPE film in the 410nm band under different cycle times is shown in Figure 4 It can be seen that the optical contrast of the first cycle is 57.5-35=22.5, and the optical contrast of the 300th cycle is 52.5-37.5=15.0, that is, the contrast of the PPTPATPE film remains at 66% of the original after 300 cycles; Figure 6 The transmittance variation curve of PPTPATPE film in the 600nm band under different cycle times is shown in Figure 6 It can be seen that the optical contrast of the first cycle is 74.5-55=19.5, and the optical contrast of the 500th cycle is 70-52.5=17.5, that is, the contrast of the PPTPATPE film remains at 89% of the original after 500 cycles, indicating that the PPTPATPE film obtained by the present invention has excellent color change stability.
[0081] Figure 5 The response time kinetic change curve of PPTPATPE film in the 410nm band at different times is shown in Figure 2. Figure 5 As shown, the coloring time of the PPTPATPE film at 410nm is 0.95s, and the fading time is 1.78s (the coloring time of the existing film is 1.5s, and the fading time is 1.8s); Figure 7 The response time kinetic change curve of PPTPATPE film in the 600nm band at different times is shown in Figure 2. Figure 7 As shown, the coloring time of the PPTPATPE film at 600nm is 1.8s, and the fading time is 1.4s, which indicates that the PPTPATPE film prepared by the present invention has a fast response speed.
[0082] It can be seen from the above embodiments that the present invention provides a tetraphenylethylene polymer. The electrochromic film prepared from the tetraphenylethylene polymer has high optical contrast, fast response speed and good stability, and is expected to be used in the fields of display, anti-counterfeiting and biological analysis.
[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A tetraphenylethylene polymer, characterized in that It has the structure shown in formula I: Wherein, n=20-1000, and n is an integer.
2. The method for preparing the tetraphenylethylene polymer according to claim 1, characterized in that: The following steps are involved: Mixing a monomer having a structure represented by formula II and a compound having a structure represented by formula Ш with an alkali reagent, an additive, a catalyst, and an organic solvent to carry out an arylation polycondensation reaction to obtain a tetraphenylethylene polymer; 3. The preparation method according to claim 2, characterized in that: The mass ratio of the monomer having the structure shown in formula II to the compound having the structure shown in formula Ш is 1-2:1; the alkaline reagent includes potassium carbonate or sodium carbonate; the additive includes pivalic acid or pivalic acid; the catalyst includes palladium acetate or tetrakistriphenylphosphine palladium; the mass ratio of the alkaline reagent, the additive, the catalyst and the compound having the structure shown in formula Ш is 1.17-1.5:1:1.43-2:1.5-2; the organic solvent includes DMAc or DMF.
4. The preparation method according to claim 2, characterized in that: The temperature of the arylation polycondensation reaction is 125-135° C. and the time is 12-20 hours.
5. Use of the tetraphenylethylene polymer according to claim 1 or the tetraphenylethylene polymer prepared by the preparation method according to any one of claims 2 to 4 in a display device.
6. The use according to claim 5, characterized in that: The tetraphenylethylene polymer is applied to a display device in the form of an electrochromic film.
7. The use according to claim 5, characterized in that: The electrochromic film comprises a substrate and an electrochromic layer supported on the substrate; the material of the electrochromic layer is the tetraphenylethylene polymer described in claim 1 or the tetraphenylethylene polymer prepared by any one of the preparation methods of claims 2 to 4.
8. The use according to claim 7, characterized in that: The substrate includes indium tin oxide conductive glass, fluorine tin oxide conductive glass or polyethylene terephthalate conductive substrate.
9. The use according to claim 7, characterized in that: The electrochromic layer is formed on the surface of the substrate by solution processing film forming method.
10. The use according to claim 9, characterized in that: The solvent used in the solution processing film-forming method includes dichloromethane, chloroform, tetrahydrofuran, toluene or dimethylformamide.